The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/bcp.14166
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1/1b study of PUR1900, an inhaled formulation of itraconazole, in healthy volunteers and asthmatics to study safety, tolerability and pharmacokinetics

Abstract: Aims Oral itraconazole has variable pharmacokinetics and risks of adverse events associated with high plasma exposure. An inhalation formulation of itraconazole (PUR1900) is being developed to treat allergic bronchopulmonary aspergillosis, an allergic inflammatory disease occurring in asthmatics and patients with cystic fibrosis. Methods A 3‐part, open‐label Phase 1 study was conducted to evaluate safety, tolerability and pharmacokinetics of PUR1900. Healthy volunteers (n = 5–6/cohort) received either single (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…More recently, PC1244 has shown activity against azole‐resistant A fumigatus 46 . In addition, an early phase randomized controlled trial (RCT) of PUR1900, a dry powder itraconazole preparation has shown good safety and tolerability, higher lung and lower plasma concentration compared with oral treatment 47 . Identifying children who may benefit from these treatments for inclusion in clinical trials would be an important clinical advance.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, PC1244 has shown activity against azole‐resistant A fumigatus 46 . In addition, an early phase randomized controlled trial (RCT) of PUR1900, a dry powder itraconazole preparation has shown good safety and tolerability, higher lung and lower plasma concentration compared with oral treatment 47 . Identifying children who may benefit from these treatments for inclusion in clinical trials would be an important clinical advance.…”
Section: Discussionmentioning
confidence: 99%
“…No current trials for PC945 are listed on clincaltrials.gov although a phase III trial is slated for 2021 in patients with refractory or resistant pulmonary fungal disease [65].…”
Section: Pc945mentioning
confidence: 99%
“…A Phase 1 study in healthy volunteers and adult asthmatic patients (NCT03479411) demonstrated that PUR1900 was safe and well-tolerated. Compared to oral dosing, PUR1900 achieved higher lung and lower plasma itraconazole exposure relative to oral itraconazole treatment [ 92 ]. After a single dose of inhaled PUR1900 in asthmatics, therapeutic itraconazole sputum concentrations were observed for over 24 hours in most patients [ 92 ].…”
Section: Pur1900: Inhaled Itraconazolementioning
confidence: 99%